EVALUASI PEMBELAJARAN BAHASA ARAB BERDASARKAN KECERDASAN MAJEMUK PADA SISWA BERBAKAT - Anah, Saiul; Isa, Abdullah (Al-Fakkaar, 2025)
Evaluation of an Arabic learning program involves a series of activities based on an adequate theoretical basis, followed by systematic planning and steps. The aim is to determine students' success in learning Arabic. The theory of multiple intelligences was proposed by Howard Gardner. This research uses library research. Library research is research that aims to collect data and information with the help of various materials contained in the library, for example books, notes, papers, and so on. Multiple intelligences allow students to develop the abilities they already have. Environmental conditions that are conducive and in harmony with their intelligence enable a person to develop their intelligence to the maximum. This can be done by conducting learning that contains the values of each intelligence.